A Family Affair: Populism, Technocracy, and Political Epistemology. Issue 1 (2nd July 2020) - Elliott, Kevin J.
ABSTRACT: Jeffrey Friedman's Power Without Knowledge provides not only a critique of technocracy but a compelling story about the intimate relationship between three of today's most important political phenomena: populism, technocracy, and democracy. In contrast to many recent accounts that treat populism as a backlash against technocracy, Friedman's theory suggests that populism is a lineal descendent of technocracy, with which it shares substantial intellectual DNA. Friedman's implicit theory of populism helps to explain many of its core features, including its political stances, emotionality, and hostility to mediating institutions, in interpretively charitable ways. Central to Friedman's analysis is the importance of political epistemology, which supplies key connective tissue between the three phenomena. The relations between technocracy, democracy, and populism revealed by Friedman's theory generate both enlightening and disturbing implications for democratic theory.